High‐intensity focused ultrasound for treatment of pancreatic cancer: a systematic review. Issue 4 (December 2014) - Li, Cui Cui; Wang, Ying Qiang; Li, You Ping; Li, Xiang Lian
Abstract Objective To explore the efficacy and safety of high‐intensity focused ultrasound combined with other physical therapies for the treatment of pancreatic cancer, so as to provide reference for clinical application. Methods The PubMed, EMbase, The Cochrane Library (Issue 11, 2013), CBM, CNKI, and WanFang databases were systematically searched up to November 2013. The randomized controlled trials and clinical controlled trials about the treatment of high‐intensity focused ultrasound were included. According to the inclusion and exclusion criteria, two reviewers independently screened the studies, exacted the data, and assessed the quality. The meta‐analysis was performed by using the RevMan 5.0 software. Results A total of 23 studies including 19 randomized controlled trials and four clinical controlled trials were included. Of which 14 studies reported the safety. The results of meta‐analyses showed that: the survival rate at 6 months and 12 months, overall efficacy, and clinical benefit rate in high‐intensity focused ultrasound plus radiation and chemotherapy group were significantly higher than those in groups treated with three‐dimensional conformal radiation therapy (P < 0.05), gemcitabine (P < 0.05), gemcitabine plus cisplatin (P < 0.05), and gemcitabine plus 5‐fluorouracil (P < 0.05). The adverse effect caused by high‐intensity focused ultrasound plus other therapy was equal to those in the control group. The major high‐intensity focused ultrasound‐related adverse effect was skin damage and fever. Conclusion The current evidence suggested that the efficacy of high‐intensity focused ultrasound for pancreatic cancer was superior to other therapies. However, the poor quality of trails may reduce the reliability of outcome to some extent. The current evidence suggested that the efficacy of HIFU for pancreatic cancer was superior to other therapies, but with poor quality. Therefore, a standard and unified criterion for the diagnosis and outcome measures of pancreatic cancer is needed, and the quality of study design and implementation should be bettered, so as to improve the high quality of evidence for its clinical application.